Fluid Therapy in Dogs and Cats With Sepsis - Montealegre, Federico; Lyons, Bridget M. (Frontiers in Veterinary Science, 2021)
Sepsis is currently defined as life-threatening organ dysfunction caused by a dysregulated host response to infection. Sepsis may occur secondary to infection anywhere in the body, and its pathogenesis is complex and not yet fully understood. Variations in the host immune response result in diverse clinical manifestations, which complicates clinical recognition and fluid therapy both in humans and veterinary species. Septic shock is a subset of sepsis in which particularly profound circulatory, cellular, and metabolic abnormalities are associated with a greater risk of mortality than with sepsis alone. Although septic shock is a form of distributive shock, septic patients frequently present with hypovolemic and cardiogenic shock as well, further complicating fluid therapy decisions. The goals of this review are to discuss the clinical recognition of sepsis in dogs and cats, the mechanisms of its pathogenesis, and considerations for fluid therapy. Important pathophysiologic changes such as microvascular alterations, damage to the endothelial glycocalyx, hypoalbuminemia, and immune paralysis will be reviewed. The advantages and disadvantages of treatment with crystalloids, natural and synthetic colloids, and blood products will be discussed. Current recommendations for evaluating fluid responsiveness and the timing of vasopressor therapy will also be considered. Where available, the veterinary literature will be used to guide recommendations.